PENGUATAN PENDIDIKAN AKHLAK SISWA MELALUI PROGRAM BINA PRIBADI ISLAMI (BPI) DI SMP ISLAM TERPADU AL-USWAH SURABAYA - hidayanto, anang; rohmaniyah, vivid (UNIVERSITAS MUHAMMADIYAH SURABAYA, 2024)
This research aims to discuss: (1) How to plan for strengthening student morals through the Islamic Personal Development Program (BPI) at Al-Uswah Integrated Islamic Middle School, Surabaya; (2) How to Strengthen Students' Morals through the Islamic Personal Development Program (BPI) at Al-Uswah Integrated Islamic Middle School, Surabaya; (3) How to evaluate the strengthening of student morals through the Islamic Personal Development Program (BPI) at Al-Uswah Integrated Islamic Middle School, Surabaya. This research is a type of field research using a qualitative approach. Data collection techniques in this research used observation, interview and documentation techniques. Data analysis in the form of data sources, techniques and data analysis. The data analysis technique is descriptive analysis consisting of data reduction, data presentation and drawing conclusions. The result of this research found that strengthening students’ moral education through the Islamic Personal Development program (BPI) at Al-Uswah Integrated Islamic Middle School Surabaya consisted of planning which included determining goals, determining the curriculum, determining competent human resources, grouping and scheduling. Implementation includes moral education related to Allah SWT, morals related to humans and morals related to the environment and evaluation ehich includes evaluation of work program achievements, evaluation of educational resources and evaluation of obstacles Penelitian ini bertujuan untuk membahas: (1) Bagaimana Perencanaan Penguatan Akhlak Siswa Melalui Program Bina Pribadi Islami (BPI) di SMP Islam Terpadu Al-Uswah Surabaya; (2) Bagaimana Pelaksanaan Penguatan Akhlak Siswa Melalui Program Bina Pribadi Islami (BPI) di SMP Islam Terpadu Al-Uswah Surabaya; (3) Bagaimana Evaluasi Penguatan Akhlak Siswa Melalui Program Bina Pribadi Islami (BPI) di SMP Islam Terpadu Al-Uswah Surabaya. Penelitian ini merupakan jenis penelitian lapangan dengan menggunakan pendekatan kualitatif. Teknik pengumpulan data dalam penelitian ini menggunakan teknik observasi, wawancara dan dokumentasi. Tiangulasi data berupa sumber data, teknik dan analisis data. Teknik analisis data berupa analisis deskriptif yang terdiri dari reduksi data, penyajian data dan penarikan kesimpulan. Hasil penelitian ini ditemukan bahwa dalam peguatan pendidikan akhlak siswa melalui program Bina Pribadi Islami (BPI) di SMP Islam Terpadu Al Uswah Surabaya terdiri dari, perencanaan yang meliputi penentuan tujuan, penentuan kurikulum, penentuan sumber daya manusia yang kompeten, pengelompokan dan penjadwalan. Pelaksanaan yang meliputi pendidikan akhlak yang berkaitan dengan Allah, akhlak yang berkaitan dengan manusia dan akhlak yang berkaitan dengan lingkungan dan Evaluasi yang meliputi evaluasi capaian program kerja, evaluasi sumber daya pendidikan dan evaluasi hambatan.